Juridical Review of the Authority of the Central Jakarta District Court in Deciding Election Postponement Cases (Central Jakarta District Court Decision Study Decision Number 757/Pdt.G/2022/PN Jkt. Pst) - Lavienda William; Tanissa Mayra Tsabitha; Sitti Nabila Yusri (CV. Rayyan Dwi Bharata, 2023)
Indonesia is a unitary state in the form of a republic that adheres to an indirect democratic system of government, in which the people's voice is represented by the people's representative body so that the state always carries out a general election system every 5 years. General elections are a means of people's sovereignty to elect members of the DPR, DPD, DPRD, President and Vice President, which are carried out directly, publicly, freely, confidentially, honestly and fairly, within the Unitary State of the Republic of Indonesia based on Pancasila and the 1945 Constitution of the Republic of Indonesia. issues circulating in Indonesia regarding elections because Indonesia will again carry out elections in 2024. One of the issues that has shocked the public lately is the issue of postponing the elections that came from the Central Jakarta District Court. The research method used in writing this scientific article is normative juridical research. As for the research approach used in this study is qualitative research. From the results of the research, the authors conclude that the election dispute between the Prima Party and the KPU does not fulfill the conditions for postponement of the election, and that the Central Jakarta District Court is not authorized to adjudicate cases of postponed elections. Court institutions in the future are expected to carry out their duties and authorities in accordance with applicable laws and regulations.